2016
DOI: 10.1177/0956462416632428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of non-AIDS causes of death among HIV-infected individuals receiving antiretroviral therapy: a systematic review and meta-analysis

Abstract: The advent of antiretroviral therapy has significantly improved AIDS-related morbidity and mortality. Yet, among people living with HIV, deaths due to non-AIDS-defining illnesses have been on the rise. The objective of this study was to provide information about the global prevalence and distribution of non-AIDS causes of death in the last ten years among people living with HIV receiving antiretroviral therapy, by income levels of countries. We used broad search terms in Google Scholar, PubMed, and EMBASE to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 40 publications
5
109
0
5
Order By: Relevance
“…Over 60% of the coded causes of death in ART-CC were due to NADEs. This is consistent with the findings from a recent systematic review and meta-analysis which estimated the pooled proportion of patients with death due to NADEs in high-income countries during the ART era was 54% (95% CI 46% to 62%) [37]. The most frequent cause of NADE death in our study was non-AIDS malignancies (24%) followed by accidents/suicides/overdoses (17%), cardiovascular deaths (16%), non-AIDS infections (15%) and hepatic deaths (13%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Over 60% of the coded causes of death in ART-CC were due to NADEs. This is consistent with the findings from a recent systematic review and meta-analysis which estimated the pooled proportion of patients with death due to NADEs in high-income countries during the ART era was 54% (95% CI 46% to 62%) [37]. The most frequent cause of NADE death in our study was non-AIDS malignancies (24%) followed by accidents/suicides/overdoses (17%), cardiovascular deaths (16%), non-AIDS infections (15%) and hepatic deaths (13%).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the crude mortality rate per 1000 p‐y due to NADEs (5.26 (95% CI 5.09 to 5.42)) was slightly higher than that reported from other cohorts in high‐income countries, including South Korea (3.71, 95% CI 2.52 to 5.48) 35, Spain (3.75, 95% CI 2.84 to 4.94) 36, and from the Data collection on Adverse Events of anti‐HIV Drugs (D:A:D) cohort in Australia, Europe, and the United States (4.28, 95% CI 4.06 to 4.53) 12, 37–the latter two have some overlap with our dataset. It is possible this finding is related to differences in baseline CD4+ count (342 cells/mm 3 (IQR 163 to 546) in Spain, 400 (IQR 242 to 590) in D:A:D, and 244 (IQR 116 to 369) for ART‐CC, respectively) as several previous studies have described lower CD4+ counts as risk factors for NADE mortality 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, people living with HIV (PLWH) now live long enough to face conditions that were traditionally seen in the elderly, such as cardiovascular disease (CVD) [4]. In high-income countries, CVD is the second non-AIDS cause of death in people living with HIV infection, and it is a significant contributor to non-AIDS deaths in developing and sub-Saharan countries [57]. Studies have shown that HIV-infected individuals are at higher risk of several cardiovascular abnormalities, such as coronary artery disease (CAD) [8, 9], heart failure and heart failure admission [10], subclinical atherosclerosis of coronary [1113] and carotid arteries [8, 14, 15], global and regional left ventricular (LV) systolic function [16], LV diastolic dysfunction [16, 17], myocardial fibrosis and steatosis [9, 18], pulmonary hypertension [19], stroke [20], atrial fibrillation [21], and sudden cardiac death [22].…”
Section: Introductionmentioning
confidence: 99%
“…People living with HIV (PLWH) have higher levels of morbidity and mortality than the general population (Farahani et al, 2016). The non-AIDS related mortality rates are largely attributable to cardiovascular disease (Farahani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The non-AIDS related mortality rates are largely attributable to cardiovascular disease (Farahani et al, 2016). Current hypotheses link the increased incidence of these comorbidities to side-effects of antiviral therapy (Dillon et al, 2013;El-Sadr, 2007), HIV-related chronic inflammation (Hearps et al, 2014) and modifiable lifestyle factors, such as increased tobacco use (Lifson and Lando, 2012) and decreased physical activity (Schuelter-Trevisol et al, 2012).…”
Section: Introductionmentioning
confidence: 99%